Biodiversitas Ikan Karang Pada Terumbu Karang Buatan Dengan Metode Mars Artificial Reef Restoration System (MARRS) di Situs Restorasi Terumbu Karang Perairan Padangbai, Karangasem, Bali - Damar, Aryo; Wiyanto, Dwi Budi; Putra, I Dewa Nyoman Nurweda (Bumi Lestari, 2025)
Coral reefs have high ecological and economic value, but the management of coral reef ecosystems is still poor, so that coral reefs suffered from direct or indirect anthropogenic activities. Hence, since 2019 there have been two coral reef rehabilitation sites in Padangbai waters managed by private diving companies and collaborating with the community and local government in efforts to restore the condition of the coral reefs and rehabilitate the local reef fish population. At the rehabilitation site, coral transplantation efforts were made using the Mars Assisted Reef Restoration System method, here in after referred to as MARRS. This research was conducted in March 2022 using the Underwater Visual Census (UVC) method to collect data on the diversity, abundance and biomass of reef fish at two coral reef restoration sites, Gili Mimpang and Baung Turtle in Padangbai Waters, Karangasem, Bali. Based on the results of this study, the diversity index obtained at the Gili Mimpang and Baung Turtle sites is 3.23 and 2.60 respectively. Gili Mimpang is categorized as having high biodiversity (H'> 3.0) and Baung Turtle is categorized as having moderate biodiversity. The total biomass of reef fish at the Gili Mimpang and Baung Turtle sites was 246.25 kg/ha and 109.51 kg/ha respectively.